Training Programs Designed for Muscle Hypertrophy in Bodybuilders: A Narrative Review - Ragami C. Alves; Jonato Prestes; Alysson Enes; Wilson M. A. de Moraes; Thiago B. Trindade; Belmiro F. de Salles; Alan A. Aragon; Tacito P. Souza-Junior (MDPI AG, 2020)
Bodybuilding is a sport that requires adequate training strategies in order to maximize skeletal muscle hypertrophy. The purpose of the present review was to perform a narrative assessment of the training routines designed for muscle hypertrophy used by bodybuilders. A search was carried out in the databases Pubmed/MEDLINE, Scielo, EBSCO, LILACS, SportDiscus, Web of Science, and CINAHL with the words "Resistance training" and "hypertrophy" in bodybuilders and their variations that involve the respective outcomes. Fourteen studies were identified that investigated the long-term training routines of bodybuilders. These studies demonstrate a pattern in the training organization, whereby there is a separation of training into four distinct periods: off-season, pre-contest, peak week, and post-contest. Each period has a specific spectrum of intensity load, total training volume, and exercise type (multi- or single-joint). We conclude that bodybuilding competitors employed a higher intensity load, lower number of repetitions, and longer rest intervals in the off-season than pre-contest.